Inkheart - Softley, Iain; Pokorny, Diana; Funke, Cornelia Caroline; Warner Home Video; New Line Home Entertainment (Los Angeles, CA : New Line Home Entertainment, 2009, 2009)
When Mo Folchart reads a story aloud, the characters leap off the page. Literally. And that's a problem. One night he brings out three characters from Inkheart, a story set in medieval times and filled with magical beings. Capricorn and Basta are two villains. Dustfinger is a fire-eater. Now, 10 years later Mo's daughter, Meggie, discovers the truth and it's up to her to escape Capricorn's evil grasp. Mo has been searching for a long lost book that will help so he can use his special powers to send the interlopers back to their world
Title from title screen
Based on the novel by Cornelia Funke
Director of photography, Roger Pratt ; editor, Martin Walsh ; music, Javier Navarrete ; production designer, John Beard ; costume designer, Verity Hawkes
Cast: Brendan Fraser, Sienna Guillory, Eliza Hope Bennett, Richard Strange, Paul Bettany, Helen Mirren, Rafi Gavron, Andy Serkis, Jim Broadbent
DVD format
With optional Chinese, english or Malay subtitles
Keywords: Funke, Cornelia Caroline -- Film and video adaptations; Good and evil -- Drama; Oral reading -- Drama; Fathers and daughters -- Drama